Ballistic Resistance of Honeycomb Sandwich Panels under In-Plane High-Velocity Impact - Chang Qi; Shu Yang; Dong Wang; Li-Jun Yang (The Scientific World Journal)
The dynamic responses of honeycomb sandwich panels (HSPs) subjected to in-plane projectile impact were studied by means of explicit nonlinear finite element simulations using LS-DYNA. The HSPs consisted of two identical aluminum alloy face-sheets and an aluminum honeycomb core featuring three types of unit cell configurations (regular, rectangular-shaped, and reentrant hexagons). The ballistic resistances of HSPs with the three core configurations were first analyzed. It was found that the HSP with the reentrant auxetic honeycomb core has the best ballistic resistance, due to the negative Poisson’s ratio effect of the core. Parametric studies were then carried out to clarify the influences of both macroscopic (face-sheet and core thicknesses, core relative density) and mesoscopic (unit cell angle and size) parameters on the ballistic responses of the auxetic HSPs. Numerical results show that the perforation resistant capabilities of the auxetic HSPs increase as the values of the macroscopic parameters increase. However, the mesoscopic parameters show nonmonotonic effects on the panels' ballistic capacities. The empirical equations for projectile residual velocities were formulated in terms of impact velocity and the structural parameters. It was also found that the blunter projectiles result in higher ballistic limits of the auxetic HSPs.